SYSTEMIC APPROACH TO INCENTIVE ATHLETES IN BULLET SHOOTING - Grigan, S.A.; N.V. , Ryzhkin; Korobov, I.A.; Soprunov, N.I. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the most effective methods of stimulation for those involved in bullet shooting. Methods and structure of the study. The experiment involved two groups involved in bullet shooting, at the Army Sports Club (ASC) in St. Petersburg, 100 athletes (50 in the experimental and 50 in the control groups) with I and II sports categories. Results and conclusions. The physical preparation of the shooter is necessary, first of all, for psychological stability when aiming, when certain muscle groups are activated and every action must be coordinated at the subconscious level, up to the shot itself. Therefore, the universality of a systematic approach to stimulating those involved in shooting, when special attention is paid to psychological motives. Consequently, the universality of a systematic approach to stimulating those involved in shooting, when special attention is paid to psychological motives, spiritual qualities, character development, will and concentration, including on the basis of Zen philosophy, is the most productive.